THE EFFECT OF EMPOWERMENT AND HUSBAND SUPPORT PROGRAM ON BREASTFEEDING BEHAVIOR AND SUCCESS OF BREASTFEEDING AMONG ADOLESCENT PREGNANT WOMEN - Lahukarn, Benjawan; Noonart, Tassanee; Rattaya, Maliwan; Boonrat, Wanpen (Journal of MCU Nakhondhat, 2020)
The article of this research has objective to study the effects of empowerment programs with the support of husbands on breastfeeding behavior and breastfeeding success in first - term adolescent mothers. Using Gibson's empowerment theory. The sample was the first adolescent pregnant woman. Pregnant from 32 weeks to gestation before 37 weeks of antenatal care. One hospital in Nakhon Si Thammarat. The sample was selected by simple random sampling according to the selection criteria of 50 persons, divided into two groups 25 people in the experimental group received the empowerment program with the support of the husband. And control group Receive regular nursing care. The experimental tool was an empowerment program in conjunction with the husband's journey. The tools used for data collection consisted of a questionnaire consisting of 3 parts: personal record Knowledge assessment form for breastfeeding and an attitude assessment form regarding breastfeeding. Breastfeeding behavior assessment form and tools used to direct the experiment Is a record of breastfeeding behavior practice For the first teenage mother. The data were analyzed by means of frequency, percentage, mean, standard deviation, and T - tests. The study found that The experimental group after receiving the program They had mean scores on knowledge, attitudes and breastfeeding behavior. Were significantly higher than before and than the control group (p <.001, p <.001, p <.001, respectively).The results of this study revealed that the empowerment program with the support of the husband It will help pregnant women, adolescent first pregnancies, to have proper breastfeeding habits. Lead to success in breastfeeding.